2003
DOI: 10.1152/ajpheart.00718.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular regulation and expressions of NO synthase-tyrosine hydroxylase in nucleus tractus solitarius of ovine fetus

Abstract: Ma, Sheng-Xing, Qun Fang, Brian Morgan, Michael G. Ross, and Conrad R. Chao. Cardiovascular regulation and expressions of NO synthase-tyrosine hydroxylase in nucleus tractus solitarius of ovine fetus. Am J Physiol Heart Circ Physiol 284: H1057-H1063, 2003. First published December 5, 2002; 10.1152/ajpheart.00718.2002The purpose of this study was to examine cardiovascular responses to fourth cerebral ventricle (4V) administration of nitroglycerin (NTG) or an inhibitor of nitric oxide (NO) synthase (NOS) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(71 reference statements)
0
4
0
1
Order By: Relevance
“…Chan et al (3) have reported pharmacologic data demonstrating roles for both iNOS and nNOS as modulators of neuronal mechanisms controlling cardiovascular function. Ma and colleagues (14) have presented data that suggest that reflex activity might be modulated by the synthesis and release of nitric oxide in the relevant brainstem nuclei. If so, developmental changes in the activity of the baroreflex might be partly explained by an ontogenetic change in the capacity for biosynthesis of nitric oxide in these brainstem nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chan et al (3) have reported pharmacologic data demonstrating roles for both iNOS and nNOS as modulators of neuronal mechanisms controlling cardiovascular function. Ma and colleagues (14) have presented data that suggest that reflex activity might be modulated by the synthesis and release of nitric oxide in the relevant brainstem nuclei. If so, developmental changes in the activity of the baroreflex might be partly explained by an ontogenetic change in the capacity for biosynthesis of nitric oxide in these brainstem nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…nNOS expression in the medulla has been reported by numerous laboratories and is widely regarded as the major nitric oxide-producing enzyme in medullary neurons (14). As such, nNOS expression is well characterized in the nucleus tractus solitarius, as well as other medullary regions important for baroreceptor and chemoreceptor reflex function (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, the locations of TH-positive neurons is not restricted to known cell groupings. Immuno histochemical reactions for TH demonstrated monoaminergic neurons in the SolTN, where their numbers have been assessed by different authors as 12-18% [19,20]. We did not fi nd any convincing data demonstrating the presence and numbers of TH-positive neurons in other vasomotor nuclei with active roles in the mechanisms regulating the circulation.…”
Section: Discussionmentioning
confidence: 62%
“…This conclusion also has morphological grounds: in the SolTN, for example, along with TH-positive neurons, up to 14% of NADPH-d-positive neurons were seen, some of which (about 8%) were colocated with TH-immunopositive cells [10,19] although other data indicate that only 3% of TH-positive neurons in the rat brainstem are colocated with nNOS-containing cells [13]. Considering that the locations and quantitative distributions of NADPH-d and nNOS in nuclei have quite often failed to coincide in our previous studies [6,7], we used a more specifi c immunohistochemical reaction for nNOS to detect NO neurons.…”
Section: Discussionmentioning
confidence: 84%
“…Известно также, что в физиологических условиях NO облегчает процессы передачи сенсорной информации внутри ЯСТ, обеспечивая тем самым барорецепторное торможение СНС и стабильный уровень АД [8]. Микроинъекции в это ядро блокаторов синтеза NO, напротив, стимулируют увеличение электрической активности симпатических нервов и повышение АД [16,17].…”
Section: Discussionunclassified